2022
DOI: 10.36740/wlek202201213
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of the Formation of Motor-Secretory Disorders in Patients With Gerd With Concomitant Ait

Abstract: The aim: The aim of this work was to study the effect of thyroid hormones on motor-secretory dysfunction in patients with GERD with concomitant AIT. Materials and methods: The study involved three groups of patients: with isolated GERD, GERD with AIT at the stage of hypothyroidism and GERD with AIT at the stage of hyperthyroidism. The control group consisted of 15 practically healthy individuals. GERD and AIT were diagnosed on the basis of ICD-10. All patients underwent a comprehensive examination, including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…As much as 50-100% of gastric acid secretion increases after long-term PPI use. Meanwhile, a systematic review of the evaluation of acid hypersecretion showed that there was a rebound after 8 weeks of PPI use [12].…”
Section: Profile Of Length Of Time For Gastric Acid Disorders or Comb...mentioning
confidence: 99%
“…As much as 50-100% of gastric acid secretion increases after long-term PPI use. Meanwhile, a systematic review of the evaluation of acid hypersecretion showed that there was a rebound after 8 weeks of PPI use [12].…”
Section: Profile Of Length Of Time For Gastric Acid Disorders or Comb...mentioning
confidence: 99%